2014
DOI: 10.1021/la503413w
|View full text |Cite
|
Sign up to set email alerts
|

Coverage and Disruption of Phospholipid Membranes by Oxide Nanoparticles

Abstract: We studied the interactions of silica and titanium dioxide nanoparticles with phospholipid membranes and show how electrostatics plays an important role. For this, we systematically varied the charge density of both the membranes by changing their lipid composition and the oxide particles by changing the pH. For the silica nanoparticles, results from our recently presented fluorescence vesicle leakage assay are combined with data on particle adsorption onto supported lipid bilayers obtained by optical reflecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 39 publications
2
28
1
Order By: Relevance
“…Vesicle preparation was performed similarly to previous work. 42,43 In short, we mixed phospholipids together in the desired ratio in a round bottom flask, evaporated the chloroform under a stream of nitrogen and dried the lipid film under vacuum for at least 2 h. After drying, the lipids were resuspended in the appropriate buffer to a final lipid concentration (C l E 2.0 Â 10 À2 M) and hydrated for about 1 h in a rotary evaporator (no vacuum, 323 K, 100 rpm). This resulted in multilamellar vesicles.…”
Section: Vesicle Preparationmentioning
confidence: 99%
“…Vesicle preparation was performed similarly to previous work. 42,43 In short, we mixed phospholipids together in the desired ratio in a round bottom flask, evaporated the chloroform under a stream of nitrogen and dried the lipid film under vacuum for at least 2 h. After drying, the lipids were resuspended in the appropriate buffer to a final lipid concentration (C l E 2.0 Â 10 À2 M) and hydrated for about 1 h in a rotary evaporator (no vacuum, 323 K, 100 rpm). This resulted in multilamellar vesicles.…”
Section: Vesicle Preparationmentioning
confidence: 99%
“…[11][12] To evaluate the risks of exposure to inhaled nanomaterials, recent studies have been focusing on the interaction of particles with membranes, more specifically on model systems made of DMPC (1,2-dimyristoyl-sn-glycero-3-phosphocholine) or DOPC (1,2-dioleoyl-sn-glycero-3phosphocholine) unilamellar vesicles. [13][14][15][16][17][18][19][20] The review of the different interaction potentials between particles and membranes revealed the importance of the interplay between particle/vesicle attraction and bilayer bending energy. 17 For diameters lower than a critical size (order of 10 nm for silica), the particles decorate the outer surface of the membrane, and induce aggregation.…”
Section: -Introductionmentioning
confidence: 99%
“…[9,10,11,12,13,14,15,16]. The levels of detail used to represent the molecules in these models fall roughly in two main categories: high-resolution and low-resolution.…”
Section: Introductionmentioning
confidence: 99%